(untitled) (GEOMATE Journal, 2018)
This study investigates the hydro-environmental condition of Dibawah Lake, Province of Western Sumatra, Indonesia, using a finite element model called the Surface-water Modeling System (SMS). The aim is to present the parameters distribution in the existing condition and a year later. Field measurements are carried out to supply data for the domain input, boundary conditions, and model validation. The field measurements are lake-bed elevation, water level, current flow, and contaminant quantity measurements. The contaminant measurements are carried out to collect biochemical oxygen demand (BOD), sulfide, and total suspended sediment (TSS). The existing flow model is validated by current flow and water elevation field data. The validation shows a decent agreement. The result of water quality modeling, using the water quality module of SMS called RMA4, shows that after a year the BOD content is still in an acceptable proportion, which is less than 2 mg/liter. However, it is found that the sulfide content exceeds the limit defined by the government regulation, at over 0.002 mg/liter. In the sedimentation model generated by the module in SMS called SED2D, the maximum bed change obtained is around 15 cm, located at the inlet of two rivers connected to the lake. The proposed mitigation of the current research findings is to control the use of fertilizer around the lake watershed area with the aim of lowering the sulfide content and to maintain the lake bed elevation by routine dredging, particularly in the river inlets.